The methodology for assessing the host range of a potential paropsine parasitoid Eadya paropsidis (Braconidae) - Withers, T.M.; Allen, G.R.; Pugh, A.R. (New Zealand Plant Protection, 2016)
Classical biological control is being attempted for Paropsis charybdis (Coleoptera Chrysomelidae Chrysomelinae) an Australian eucalypt pest established in New Zealand The Australian solitary larval endoparasitoid Eadya paropsidis (Hymenoptera Braconidae) is under investigation Leaffeeding larvae of closelyrelated chrysomelid nontarget species for host range testing were examined against E paropsidis using various assays Detailed behavioural observations of E paropsidis were undertaken during 1) Nochoice sequential assays of the AB alternating with BA type (where A is the target P charybdis and B is the nontarget species); and 2) Twochoice assays of the AB type 3) In addition groups of nontarget larvae were exposed to E paropsidis under nochoice conditions for 24 hours then reared for survival to ascertain the physiological development of any parasitoid lifestages In all cases survival and development parameters of nontargets species were compared to the target P charybdis